Use of Carboxyhemoglobin as an Early Sign of Oxygenator Dysfunction in Patients Supported by Extracorporeal Membrane Oxygenation - Cousin, Vladimir L.; Giraud, Raphaël; Assouline, Benjamin; Silva, Ivo Neto; Bendjelid, Karim (Frontiers in Medicine, 2022)
Introduction Plasma free hemoglobin is the gold standard for monitoring hemolysis in extracorporeal membrane oxygenation (ECMO) but its routine use has some limitations. Carboxyhemoglobin (HbCO) is also a marker of intravascular hemolysis. We aimed to investigate HbCO as a marker of both hemolysis and oxygenator dysfunction in patients supported by ECMO. Methods Retrospective analysis of patients on ECMO in an adult ICU in a tertiary hospital. HbCO was recorded every 6 h in the 48 h before and after oxygenator change in adult patients on ECMO support with an oxygenator dysfunction and replacement. Results The investigation of 27 oxygenators replacements in 19 patients demonstrated that HbCO values progressively increased over time and then significantly decreased after oxygenator change. Median oxygenator lifespan was 14 days [interquartile range (IQR) 8–21] and there was no correlation between HbCO and oxygenator lifespan [Spearman coefficient 0.23 (p = 0.23)]. HbCO values at oxygenator change [HbCO median 2.7 (IQR 2.5–3.5)] were significantly higher than the HbCO values 1 week before [HbCO median 2.07 (IQR 1.86–2.8)] (p value < 0.001). Conclusion Our data highlight the potential role of HbCO as a novel marker for ECMO oxygenator dysfunction.